Propagation of solutes and pressure into aquifers following river stage rise. Issue 9 (4th September 2013) - Welch, Chani; Cook, Peter G.; Harrington, Glenn A.; Robinson, Neville I.
<x xml:space="preserve">Abstract</x> [1] Water level rises associated with river flow events induce both pressure and solute movement into adjacent aquifers at vastly different rates. We present a simple analytical solution that relates the travel time and travel distance of solutes into an aquifer following river stage rise to aquifer properties. Combination with an existing solution for pressure propagation indicates that the ratio of solute to pressure travel times is proportional to the ratio of the volume of water stored in the aquifer before the river stage rise and the volume added by the stage rise and is independent of hydraulic conductivity. Two‐dimensional numerical simulations of an aquifer slice perpendicular to a river demonstrate that the solutions are broadly applicable to variably saturated aquifers and partially penetrating rivers. The solutions remain applicable where river stage rise and fall occur, provided that regional hydraulic gradients are low and the duration of the river stage rise is less than pressure and solute travel times to the observation point in the aquifer. Consequently, the solutions provide new insight into the relationships between aquifer properties and distance and time of solute propagation and, in some cases, may be used to estimate system characteristics. Travel time metrics obtained for a flood event in the Cockburn River in eastern Australia using electrical conductivity measurements enabled estimates of aquifer properties and a lateral extent of river‐aquifer mixing of 25 m. A detailed time series of any soluble tracer with distinctly different concentrations in river water and groundwater may be used.